Rational Emotive Behavioral Counseling Model to Reduce Public Speaking Anxiety in College Students - Tazkia Auliya Nur Hilaliyah; Feida Noor Laila Isti'adah; Gian Sugiana Sugara (Edupotensia, 2025)
Public speaking ability is not without its challenges. One of the most common challenges is public speaking anxiety. Public speaking anxiety is a social communication disorder characterized by feelings of fear and worry when speaking in front of a large audience. This study utilized an experimental research design with a single-case research design (SCRD) using an A-B-A pattern to determine the effectiveness of Rational Emotive Behavior Counseling in reducing public speaking anxiety. The subjects of this study consisted of three students (N=3) who experienced severe public speaking anxiety and held irrational beliefs. The REBT intervention was provided in six sessions. Data were collected before, during, and after the intervention using the Nonoverlap of All Pairs (NAP) calculation to measure the effectiveness of the intervention. The results of this study showed a significant reduction in public speaking anxiety scores following the implementation of REBT counseling. This was evidenced by the effect size and RCI (Reliable Change Index) scores, which indicated significant and reliable changes. Thus, Rational Emotive Behavior Therapy was proven to be effective in reducing public speaking anxiety.